Récit de l’édification d’une équipe de recherche interdisciplinaire pour aborder la problématique de la situation de handicap au travail - Marie-José Durand (Perspectives Interdisciplinaires sur le Travail et la Santé)
In the year 2000, a team of researchers was formed in the province of Quebec to study the multiple biomechanical and organizational factors that may be involved in the prevention of work-related disability. In fact, the creation of the new team resulted from a better understanding of the research problem, with a shift from a monolithic medical model to a person-environment model within which the contribution of external systemic factors was considered. Although the recent literature underlines the importance of interdisciplinary work in research, few authors have examined the processes, conditions and individual issues of interdisciplinary collaboration. This article offers a brief presentation of the work disability paradigm and its characteristics, describes the process used to build the interdisciplinary team, and discusses the winning strategies for successful team development.